Alternative Approaches to Discrete Working Time Choice in an AGE Framework - Melanie Arntz; Stefan Boeters; Nicole Gürtzgen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
We compare two options of integrating discrete working time choice of heterogenous households into a general equilibrium model. The first, known from the literature, produces household heterogeneity through a working time preference parameter. We contrast this with a model that directly incorporates a logit discrete-choice approach into a AGE framework. On the grounds of both calibration consistency and adequate accomodation of within-household interaction, we argue that the logit approach is preferable.
Keywords: J51; J22; D58; 330; applied general equilibrium; discrete working time choice; labour market; wage bargaining; labour market reform; logit model; Arbeitszeit; Arbeitsangebot; Haushaltsökonomik; Logit-Modell; Allgemeines Gleichgewicht; Lohnverhandlungstheorie; Arbeitsmarktflexibilisierung; Wirtschaftspolitische Wirkungsanalyse; Reform; Schätzung; Theorie; Deutschland